Effect of fibrolytic enzyme treated roughage on nutrient utilization and growth performance in kids - SINGH, k K; DAS, M M (The Indian Journal of Animal Sciences, 2011)
Male local (Bundelkhandi) kids (12), weighing around 13 kg, were divided into 2 groups, T1 and T2 of 6 animals in each group. All the kids were offered similar ration consisting of dry grass and oat hay (50: 50) along with concentrate mixture. The animals of T1 served as control and were offered untreated roughage while the animals of T2 were offered fibrolytic enzyme treated (@ 4 g/kg DM) mixed roughage. The TVFA concentration was significantly higher in T2 as compared to T1. The ruminal pH, ammonia N and total N concentrations were similar in both groups. The CMCase and xylanase activity was higher in kids received enzyme treated diet as compared to untreated diet. The dry matter intake was similar in both the groups, however, the digestibility coefficient of DM, OM, NDF and cellulose were significantly higher in enzyme treated group. The N balance and average daily gain were numerically higher while the feed to gain ratio was lower in enzyme treated group. It was concluded that enzyme treatment improved the digestibility of nutrients with a little positive effect on average daily gain and feed conversion efficiency in growing kids.